Uncovering the phytochemicals of root exudates and extracts of lead (Pb) tolerant Chrysopogon zizanioides (L.) Roberty in response to lead contamination and their effect on the chemotactic behavior of rhizospheric bacteria - Kushwaha A.; Hans N.; Giri B.S.; Rene E.R.; Rani R. (My University, 2025)
The chemical composition of root exudates and root extracts from Chrysopogon zizanioides (L.) Roberty cv KS-1 was determined in the presence of lead [Pb(II)]. Hitherto, no information is available in the literature concerning the phytochemical components of root exudates of C. zizanioides. Significantly higher concentrations of total carbohydrates (26.75 and 42.62% in root exudates and root extract, respectively), reducing sugars (21.46 and 56.11% in root exudates and root extract, respectively), total proteins (9.22 and 23.70% in root exudates and root extract, respectively), total phenolic acids (14.69 and 8.33% in root exudates and root extract, respectively), total flavonoids (14.30 and 12.28% in root exudates and root extract, respectively), and total alkaloids (12.48 and 7.96% in root exudates and root extract, respectively) were observed in samples from plants growing under Pb(II) stress in comparison to the respective controls. GC–MS profiling showed the presence of a diverse group of compounds in root exudates and extracts, including terpenes, alkaloids, flavonoids, carotenoids, plant hormones, carboxylic/organic acids, and fatty acids. Among the detected compounds, many have an important role in plant development, regulating rhizosphere microbiota and allelopathy. Furthermore, the results indicated that C. zizanioides exudates possess a chemotactic response for rhizospheric bacterial strains Bacillus licheniformis, Bacillus subtilis, and Acinetobacter junii Pb1. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.